critical review of the successful CFC phase-out versus the delayed methyl bromide phase-out in the Montreal Protocol - Gareau, Brian J (International environmental agreements : politics, law and economics, 2010)
The Montreal Protocol is often described as an international environmental agreement par excellence. After all, it successfully led to the phase-out of almost 95% of all chlorofluorocarbon (CFC) use. A critical review of the Protocol's history, however, suggests that its successes are deeply entrenched in the economic opportunities that were made available to phase out CFCs. The Montreal Protocol, in other words, was a “best-case scenario” for CFC producers. This may be problematic for policymakers, ecological modernization practitioners, and other scholars who look to the Montreal Protocol for guidance in phasing out other global environmentally harmful substances and practices that are not as “economically efficient.” The shift to delay the phasing out of methyl bromide (MeBr) in the Protocol, an ozone-depleting substance used to this day primarily in strawberry and tomato production, demonstrates how even this most successful of international environmental agreements can become subject to significant setbacks when economic gains and scientific evidence are not obvious to the global powers. Furthermore, changes in what constitutes a viable exemption to the phase-out of CFCs versus MeBr marks a shift away from concern for the general functioning/welfare of society, and toward concern for the market performance of specific individuals. This shift runs parallel to a lack in economic incentives to phase out MeBr in the United States. The article demonstrates how civil society representation in ozone politics is largely dominated by industry interests, especially when scientific uncertainty is high.